Pour une réception dynamique. Théories et œuvres du XXe siècle (Itinera, 2019)
During the 20th century, political theatre urges the spectator to perform the duties of a “model” citizen. Through the analysis of the dynamism theory established by Luigi Nono in his musical theatre, this study tries to recognize the aesthetic potential of a “dynamic reception” that aims at making place for a political spectator.